Analysis of co‐medication in people with dementia. (25th January 2023) - Wurm, Raphael; Parvizi, Tandis; Goeschl, Stella; Untersteiner, Helena; Silvaieh, Sara; Stamm, Tanja; Cetin, Hakan; Reichardt, Berthold; Stögmann, Elisabeth
Abstract: Background and purpose: Dementia prevalence is increasing, with numbers projected to double by 2050. Risk factors for its development include age and cardiovascular comorbidities, which are found more often in patients with dementia and should be treated properly to improve outcomes. In this case–control study, we analysed a large population‐based prescription database to explore the patterns of co‐medication in patients with dementia. Methods: Prescription claims covering >99% of the Austrian population from 2005 to 2016 were obtained. Patients who were treated with an approved antidementia drug (ADD) were included and co‐medication exposure was recorded. A group of people not taking ADDs was matched for age, sex and follow‐up duration as a control. Results: We included 70, 799 patients on ADDs who were exposed to a mean of 5.3 co‐medications while control patients were treated with a total of 5.2 co‐medications ( p < 0.001). We found that patients on ADDs received less somatic (4.1 vs. 4.5) but more psychiatric medication (1.1 vs. 0.6; p < 0.001 for both). Patients on ADDs were less likely to be treated for pain, cardiovascular conditions or hyperlipidemia. More than 50% of patients on ADDs were treated with antidepressants or antipsychotics. Greater number of co‐medications was associated with markers of more intensive antidementia treatment. Conclusion: Patients on ADDs received more medications overall but were less frequently treated for somatic conditions known to be more prevalent in this group. Together, our data suggest that management of comorbidities in dementia could be improved to optimize outcome and quality of life.